Margaret the First : a biography of Margaret Cavendish, Duchess of Newcastle, 1623-1673 - Grant, Douglas (Heritage., 1957)
This biography is the first full-length study entirely devoted to the Duchess of Newcastle showing her metamorphosis from an imaginative, bashful child into a romantic public figure emerging as the first woman writer of her times.